Determination of K869, a Novel Oxime Reactivator of Acetylcholinesterase, in Rat Body Fluids and Tissues by Liquid-Chromatography Methods: Pharmacokinetic Study - Vanova, Nela; Hojna, Anna; Pejchal, Jaroslav; Herman, David; Malinak, David; Prchalova, Eliska; Musilek, Kamil; Karasova, Jana Zdarova (Journal of pharmaceutical sciences, 2021)
Oxime reactivators of acetylcholinesterase (AChE) represent an integral part of standard antidote treatment of organophosphate poisoning. Oxime K869 is a novel bisquaternary non-symmetric pyridinium aldoxime with two pyridinium rings connected by a tetramethylene bridge where two chlorines modify the pyridinium ring bearing the oxime moiety. Based on in vitro assays, K869 is a potent AChE and butyrylcholinesterase (BChE) reactivator. For the investigation of the basic pharmacokinetic properties of K869 after its intramuscular application, new HPLC-UV and LC-MS/MS methods were developed and validated for its determination in rat body fluids and tissues. In this study, the SPE procedure for sample pretreatment was optimized as an alternative to routine protein precipitation widely used in oxime pharmacokinetics studies. K869 oxime is quickly absorbed into the central compartment reaching its maximum in plasma (39 ± 4 μg/mL) between 15 and 20 min. The majority of K869 was eliminated by kidneys via urine when compared with biliary excretion. However, only a limited amount of K869 (65 ± 4 ng/g of brain tissue) was found in the brain 30 min after oxime administration. Regarding the brain/plasma ratio calculated (less than 1%), the penetration of K869 into the brain did not exceed conventionally used oximes.
Keywords: oximy; Chromatography, Liquid; tělesné tekutiny; Tandem Mass Spectrometry; Mass spectrometry; Oximes; krysa rodu Rattus; Oxime; Reactivator; zvířata; cholinesterasové inhibitory; tandemová hmotnostní spektrometrie; chromatografie kapalinová; Acetylcholinesterase; K869; reaktivátory cholinesterasy; Liquid chromatography; Body Fluids; Cholinesterase Reactivators; Rats; Bispyridinium oximes; Animals; Pharmacokinetics; acetylcholinesterasa; Cholinesterase Inhibitors